Supply Chain Management through Vertical Coordination in Vegetable Industry - Singh, Uma Shankar; Mishra, Uma Sankar (International Journal of Supply Chain Management, 2014)
The study provides empirical evidence of the importance of various vertical coordination variables needed for the effective implementation of vertically coordinated supply chain approach in vegetable industry for the measurement of efficient accessibility of vertical coordination effect benefits. Survey methodology has been used to collect data. Neural network model has been used to know the importance of vertical coordination variables as well the relation of vertical coordination variables with the vertical coordination effect variables. This study contributes to the literature by exploring the importance of various variables extracted from literatures which is applied specific five vegetables namely potato, brinjal, cabbage, cauliflower and okra. The participants involved in study are producers only and limited to the Odisha. Findings have very clearly mentioned the importance of variables. Further this can get used by the govt. organizations for policy formulation as well for the decision process in providing the input facility support. The outcome can be beneficial to other vegetable supply chain participants like intermediaries and entrepreneurs engaged in value addition and processing of vegetables. This study is one step further contribution to the body of knowledge on vegetable supply chain vertical coordination approach.